BIOZONAL STANDARDS: CALIBRATION PRINCIPLES, DEGREE OF SOPHISTICATION, AND INTERREGIONAL APPLICATION (SILURIAN GRAPTOLITES) - Koren T.N. (My University, 1996)
Modern geology now concentrating its attention not at individual sections, but on paleocontinents in gross, and initiated global generalizations, appeals for a unified approach to model zonal scales usable as standards in the "left" biostratigraphic column of correlation schemes. The term standard means the universally accepted model widely used in correlation practice. Ideally, the blozonal standard should represent a continuous or integrated sequence, which is itemized in details within a particular region on the basis of identical criteria and similar characteristics used to identify boundaries between zones (the first occurrence level of index species). Available biozonal standards of many Phanerozoic systems are in fact the zonal scales of geological areas, where respective series and stages were distinguished for the first time. For the Silurian System, it is the scale of graptolite zonation in the Great Britain and Pragian basin. However, long experience and more serious requirements to the resolution potential of biostratigraphic units showed that in many cases the latter are insufficiently valid for the global correlation. It is decided that the International Subcommission on Silurian Stratigraphy should use a generalized graptolite zonation in current studies on correlation schemes for the Silurian paleogeographic reconstructions. This zonation includes well-traceable biostratigraphic zones of stratotype and other regions, some of which can be coupled into greater, but better correlative, zonal units. The respective scale is assumed to be temporary, including only those correlative units, which are necessary for paleogeographic reconstructions. Current efforts to verify regional zonations and to improve the global correlation of debatable units (upper Llandovery, lower Wenlock, and Ludlow) are oriented toward the calibration of a universal zonal standard with a high resolution potential.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская